Economic Locus of Control and Emotional Intelligence As Correlates Of Money Attitude Among University Students - Chine, Bernard Chukwukelue; Ezisi, Jerome Ogochukwu; Enyeobi, Bede Ofoma; Eze, Mathew Anene (Practicum Psychologia, 2024)
Recently, Nigerian industries and organizations have lost a huge amount of both human and material resources, due to young adults/university students’ attitude towards money. For instance, their quest for money usually motivates them to indulge in different morally atrocious activities like internet fraud, armed robbery, prostitution, vandalization of organizational resources for their own selfish interest and stagnation of justice to the detriment of the poor in the society. Meanwhile past literatures have shown no known scientific study on the contributing factors that aid in the developing money attitude among young adult/university students in African culture, such as south-eastern Nigeria. Hence, the current study investigated emotional intelligence and economics locus of control as correlates of money attitude using ninety-two (92) participants randomly drawn from two faculties (Law and Social sciences) in Nnamdi Azikiwe University, Awka. They were made up 48 males (representing 52.2%) and 44 females (representing 47.8%), with their mean age of 29.90 and standard deviation of 6.10. A 29-item money attitude scale by Yamauchi and Templer (1982), a 40-item economic locus of control scale by Furnham (1986) and 17-item emotional intelligence scale by Baron and Parker (2000) was use for the study. Using Pearson moment correlation statistics two hypotheses were tested. The findings indicated that the first hypothesis which stated that there would be a positive relationship between money attitude and economic locus of control was confirmed at (r = .641, p <.00). Also, the findings indicated that the second hypothesis which stated that there would be a positive relationship between money attitude and emotional intelligence was accepted at (r = .280, <.00). The study findings implies that young adult who exhibited internal economic locus of control and also in control of their emotional intelligence exhibit strong sense of money attitude. It was recommended that government should invest more on research, workshops and seminars on the means of boasting young adult/university students’ emotional intelligence, economic locus of control and also means of positively influencing people’s attitude toward money.